INVENTARISASI GULMA PADA TANAMAN JAGUNG (Zea mays L.) DATARAN TINGGI DI DESA PALELON DAN DATARAN RENDAH DI KELURAHAN KIMA ATAS - Keren Selia Amy Assa; Pemmy Tumewu; Grace Tulungen (Universitas Sam Ratulangi, 2017)
SUMMARY This research aims to inventory the weeds associated in corn field in the highland and lowland. This research was conducted in two places on corn field in the highlands at Palelon Village Distric Modoinding Regency South Minahasa with altitude 975 metres AMSL and on corn field in at the lowlands Village Kima Atas Distric Mapanget Manado City with altitude 73 metres AMSL. Research conducted in may to june 2016. Research used survey method and data collection by using the square method with make distribution of sample plots. Weeds data analysis using the formula SDR (Summed Dominance Ratio). Observed variable that is weed species, number of weed, and dominance weed. The result obtained 10 weed species in the highland and 17 weed species in lowland area. The inventory results weed obtained three species of weed highlands has SDR value higher compared than other species that is Paspallum conjugatum with the SDR value of each strata (35,22 %, 38,77%, 37,66), Ageratum conyzoides with SDR value (28,99%, 30,15%, 25,89% ), Drymaria cordata with the SDR (8,8 %, 18,24%, 5,70%). While the three species of weeds lowland has SDR value higher compared than other species that is Cynodon dactilon with SDR every stratum is (29,70 %, 50,24 %), Sida rhombifolia with the SDR (12,12%, 23,69 %, 28,18 %), Calopogonium mucunoides with the SDR (2,95%, 14,29%, 29,09% ). From the research suggested weed control of asteraceae family can be done mechanically, chemical by using herbicides systemic. Poaceae can be done by mechanical or chemically. Key words : Weeds inventory, weed, weed corn field.